2013
DOI: 10.1016/j.pain.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of being primed with social deception upon observer responses to others’ pain

Abstract: This study examined whether priming with social deception affects responses (pain estimates, self-reported sympathy, inclination to help) towards others' pain. We further explored whether the priming effect is mediated by the valence of the patients (positive/negative), as indicated by the participants. First, participants (N=55) took part in an 'independent' delayed memory study in which they read either a neutral text about the use of the health care system (neutral condition) or a text about its misuse (soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 31 publications
7
37
1
Order By: Relevance
“…The current study is the first to examine the association between perceived injustice and in-vivo appraisals of pain and difficulty in response to common physical tasks (or in a sample composed exclusively of individuals with chronic low back pain). As noted, these tasks were modeled after an established paradigm [8][9][10] and purposefully chosen to extend the ecological validity of existing studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study is the first to examine the association between perceived injustice and in-vivo appraisals of pain and difficulty in response to common physical tasks (or in a sample composed exclusively of individuals with chronic low back pain). As noted, these tasks were modeled after an established paradigm [8][9][10] and purposefully chosen to extend the ecological validity of existing studies.…”
Section: Discussionmentioning
confidence: 99%
“…The order of movement performance did not vary across participants. The selection of these movements is modeled after De Ruddere and colleagues [8][9][10] and based upon previous findings indicating that these routine daily tasks require movement that is usually sufficient to increase pain and to elicit pain behaviour [25]. The experimenter provided instruction (without modeling) regarding performance of each movement (e.g.…”
Section: Dot-probe Taskmentioning
confidence: 99%
“…), and potential mechanisms of action. unfairness of the pain experience, and prejudicial/discriminatory beliefs or attitudes [3,18,19,20,40,87]. Type of relationship between pain observer and sufferer is likely important here.…”
Section: The Role Of Emotion Regulationmentioning
confidence: 99%
“…Additionally, there is preliminary evidence for the role of negative evaluation of the patient in the process of estimating a patient"s pain where there is no clear medical evidence [41]. De Ruddere and colleagues [10,11] found that observer negative evaluations of patients appear to generate lower observer pain estimates.…”
Section: Introductionmentioning
confidence: 99%